2009
DOI: 10.1590/s0073-47212009000300013
|View full text |Cite
|
Sign up to set email alerts
|

Soil invertebrates in southern Brazilian Araucaria forest - grassland mosaic: differences between disturbed and undisturbed areas

Abstract: ABSTRACT. Soil invertebrate distribution in Araucaria forest, grassland and edge habitats was studied in both disturbed and undisturbed areas in southern Brazil. Mean-density and taxa compositions were verified. Invertebrate densities differed between grassland and the other two habitats in the undisturbed area but not across the disturbed one. At the disturbed area taxa differed between the grassland and the other two habitats. The undisturbed area, on the other hand, presented taxa differences only between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
3
2
Order By: Relevance
“…Also, in the cultivated field Ladang 2 the intensive tillage and agricultural activity in this site led to increased stress on the diversity of invertebrates, so, the diversity was low. The present findings are in contrast to Frainer and Duarte, (2009). There was a difference in the Coleoptera between the two communities where the density was high in the disturbed fields compared to the undisturbed fields, where some coleopterans were resistant to the disturbance (Ronqui & Lopes 2006;Frainer & Duarte, 2009).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Also, in the cultivated field Ladang 2 the intensive tillage and agricultural activity in this site led to increased stress on the diversity of invertebrates, so, the diversity was low. The present findings are in contrast to Frainer and Duarte, (2009). There was a difference in the Coleoptera between the two communities where the density was high in the disturbed fields compared to the undisturbed fields, where some coleopterans were resistant to the disturbance (Ronqui & Lopes 2006;Frainer & Duarte, 2009).…”
Section: Discussioncontrasting
confidence: 90%
“…The present findings are in contrast to Frainer and Duarte, (2009). There was a difference in the Coleoptera between the two communities where the density was high in the disturbed fields compared to the undisturbed fields, where some coleopterans were resistant to the disturbance (Ronqui & Lopes 2006;Frainer & Duarte, 2009). Furthermore, there could be several explanations for differences like the physical properties of the soil, soil cover, soil moisture, soil organic matter that can be the determining factors.…”
Section: Discussioncontrasting
confidence: 71%
“…In the edge habitats of tawa ( Beilschmiedia tawa ) forests of New Zeeland a positive edge effect on millipede abundance was also demonstrated. In contrary, other studies showed no difference in millipede abundance between forest and forest edge habitats in Brasil ( Frainer and Duarte 2009 ), in South-Africa ( Weiermans and van Aarde 2003 ) and in the United Kingdom ( Riutta et al 2012 ).…”
Section: Discussionmentioning
confidence: 78%
“…The edge effect on different arthropod taxa was frequently studied during the last decades ( Coleoptera : Magura 2000, Lövei et al 2006 ; Ewers and Didham 2008 ; Isopoda : Antonovic et al 2012 ; multi-taxa approaches: Frainer and Duarte 2009 , Biereinger et al 2013 ). Millipedes were relatively little studied in the context of the edge effect, in spite of the rapid changes in temperature, soil structure and soil water content at forest edges ( Camargo and Kapos 1995 , Gehlhausen et al 2000 ) and its major influence on litter decomposition processes in forests.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the C. citriodora litterfall is considered as unpalatable for some species of the soil macrofauna, besides being a chemical barrier against the natural regeneration of native species (Frainer & Duarte, 2009;Diniz et al, 2011). Thus, the C. citriodora species is indicated as inhibitor of the natural regeneration of native forests since the decomposition and the cycling of nutrients are not favored in environments with the presence of this species (Valpassos et al, 2007;Evaristo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%